Friends or foes?: religious organizations and European institutions in the face of Russia’s war on Ukraine - Korniichuk, Iuliia (War in Ukraine, 2025)
The paper explores the challenges posed by Russia’s war against Ukraine to the relations between European institutions and religious organizations. In recent decades, with the resurgence of religion in the public sphere, European institutions have become a platform for dialogue with religious entities, including Orthodox churches, on various non-religious issues. Russia’s war in Ukraine has strained this cooperation. While the EU unequivocally condemned the invasion and supported Ukraine, many Orthodox Churches struggled to clearly name and condemn the aggression or, like the Moscow Patriarchate, openly supported the war. This article investigates the EU institutions’ responses to the involvement of the Moscow Patriarchate in the war and the challenges these responses pose.